Вы находитесь на странице: 1из 4

If a,b R and b0 show that: a. |a|= a2 b. |a/b|= |a|/|b| Answer a.

Show that |a|= a2 Recall that |a|=a if a>=0 and |a|=-a otherwise. Let a>=0. Then \sqrt{a^2} = a = |a| Suppose a<0. Then a=-b, where b>0, so |a|=b. On the other hand, a2 = (-b)2 = b2 = b = |a|

b. Show that |a/b|= |a|/|b| Consider the following cases: 1) Let a>=0, b>0. Then |a/b|= a/b = |a|/|b|. 2) Suppose a>=0, b<0. Then a/b<0, |a|=a, |b|=-b, so |a/b|= -(a/b) = a/(-b) = |a|/|b|. 3) Suppose a<0, b>0. Then a/b<0, |a|=-a, |b|=b, so |a/b|= -(a/b) = (-a)/b = |a|/|b|. 3) Finally, let a<0, b<0. Then a/b>0, |a|=-a, |b|=-b, so |a/b|= a/b = (-a)/(-b) = |a|/|b|. If x, y, z R and x z, show that x y z if |x-y| + |y-z| = |x-z|. Interpret this geometrically.

Suppose that x z, and |x-y| + |y-z| = |x-z| We have to show that Consider two cases: 1) y < x z. Then |x-y| = x-y, |y-z| = z-y Hence |x-y| + |y-z| = x-y + z-y = x+z-2y while |x-z| = z-x. So x+z-2y = z-x 2x-2y = 0 x=y which contradicts to the assumption y<x. Thus the case y < x z is impossible. 2. Similarly, assume that x z < y Then |x-y| = y-x, |y-z| = y-z Hence |x-y| + |y-z| = y-x + y-z = 2y-x-z while |x-z| = z-x So 2y-x-z = z-x 2y = 2z y=z which again contradicts to the assumption z<y. Thus the case x z < y is also impossible, so x y z

x y z.

Geometrically, the statement means that if x z, then the identity |x-y| + |y-z| = |x-z| is possible if and only if y belongs to the segment [x,z].

Find all x R that satisfy the equation |x+1| + |x-2| = 7. Answer |x+1|+|x-2|=7 Lets estimate our x using the simple property of module: |x| = { -x, x<0 x, x>0 Imagine that were dividing our rational numbers into three groups: x (-,-2), x(-2,-1), x(-1,+) we have such systems. {x+1<0 -x-1-x+2=7 x-2<0) x = -3

x+1-x+2=7 x- -x-1+x-2=7 x- x+1+x-2=7 x=4

Answer: x=-3, x=4 show if a,b R then, a. max (a,b) = (1/2)(a+b+|a-b|) and min (a,b)=(1/2)(a+b-|a-b|) b. min (a,b,c)=min(min(a,b),c) a. There are two possibilities: either ab or a<b. 1) max(a,b)=1/2 (a+b+|a-b|) If ab then (a-b)0 and thus |a-b|=(a-b). Let us see at the desired equality: 1/2 (a+b+|a-b|)=1/2 (a+b+(a-b))=1/2 (a+b+a-b)=1/22a=a On the other hand max(a,b)=a, because ab. Now lets check second case: a<b. If a<b then (a-b)<0 and thus |a-b|=-(a-b)=(b-a). Let us look at the desired equality: 1/2 (a+b+|a-b|)=1/2 (a+b+(b-a))=1/2 (a+b+b-a)=1/22b=b On the other hand max(a,b)=b, because a<b. So weve checked the equality for both cases, thus max(a,b)=1/2 (a+b+|a-b|) for any real numbers a,b R. 2) min(a,b)=1/2 (a+b-|a-b|) For second equality we can make almost the same proof. If ab then (a-b)0 and thus |a-b|=(a-b). Let us see at the desired equality: 1/2 (a+b-|a-b|)=1/2 (a+b-(a-b))=1/2 (a+b-a+b)=1/22b=b On the other hand min(a,b)=b, because ab. Now lets check second case: a<b. If a<b then (a-b)<0 and thus |a-b|=-(a-b)=(b-a). Let us look at the desired equality: 1/2 (a+b-|a-b|)=1/2 (a+b-(b-a))=1/2 (a+b-b+a)=1/22a=a On the other hand min (a,b) = a, because a<b. So weve checked the equality for both cases, thus min(a,b)=1/2 (a+b-|a-b|) for any real numbers a,bR. b. min(a,b,c)=min(min(a,b),c) Analogical to the part a. we can divide the problem into three cases:

1) If min(a,b,c)=a, then the left side of the equality is a. This means ab and at the same time ac. Lets look at the right side: min(a,b)=a, because ab. Then min(min(a,b),c)=min(a,c)=a, because ac. Thus the right side of the equality is a too. 2) If min(a,b,c)=b then the left side of the equality is b. In this case the proof is absolutely the same, just write a instead of b and write b instead of a. So ba and at the same time bc. Lets look at the right side: min(a,b)=b, because ba. Then min(min(a,b),c)=min(b,c)=b, because bc. Thus the right side of the equality is b too. 3) If min(a,b,c)=c then the left side of the equality is c. This means ca and at the same time cb. Then not knowing what is min(a,b) (it may be either a or b) we can conclude that cmin(a,b), thus min(min(a,b),c)=c. So weve checked the equality for each case and thus min(a,b,c)=min(min(a,b),c) is true for any real numbers a,b,c R.